OBSERVED AND PERCEIVED READINESS OF ENGLISH TEACHERS IN CONDUCTING TEACHING LEARNING PROCESS BASED ON 21ST CENTURY SKILLS - Lestari, Ni Made Pebriyanti; Padmadewi, Ni Nyoman; Dewi, Ni Luh Putu Eka Sulistia; Artini, Luh Putu (International Journal of Language and Literature, 2020)
The 21st century requires teachers to be able to integrate 21st century skills into the teaching learning process. A study on analyzing teachers’ readiness in conducting the teaching learning process based on 21st century skills in Bali has not been conducted yet. Hence, this study aimed at analyzing the Elementary English teachers’ readiness in conducting teaching learning process based on 21st century skills. This study which was done at SDK Marsudirini Negara School in Jembrana Regency used sequential embedded mixed-method as the design. The subject were one of the school principals and the English teacher. The data were obtained through questionnaires, observations, document analysis, and interview then analyzed quantitatively and qualitatively. The respondents perceived themselves as ready in conducting teaching learning process based on 21st century skills. However, the 21st century skills were not entirely inserted into the teaching learning process and the teachers are expected to be aware of the changes in the education field.